Ecosystem services in adaptation projects in West Africa. Issue 4 (20th August 2018) - Muthee, Kennedy Wahome; Mbow, Cheikh; Macharia, Geoffrey Mugo; Leal-Filho, Walter
Abstract : Purpose: The purpose of this paper is to assess the extent to which adaptation projects have incorporated ecosystem services, as well as their redesigning options. The projects selected are listed under National Adaptation Programme of Action in West African region. Design/methodology/approach: A desktop survey approach was used to review 168 projects from 13 countries across West Africa. The projects were categorized and analyzed according to their adaptation goal, thematic focus, their implementation duration and level of investment. Findings: The adaptation initiatives are dominated by actions in the agricultural sector accounting for 32 per cent of the total. Further, they were characterized by small grants consideration with 63 per cent falling under US1m budget, short-term implementation duration with 46 per cent having three years' execution period. A large portion of projects (55 per cent) mentioned directly one or more ecosystem services, with provisioning services being referred to in 50 per cent of the cases. Originality/value: Adaptation projects with ecosystem services components are more sustainable and beneficial to the community. Hence, more consideration of nature benefits during project design, more financial consideration and localizing of the projects to realize the global adaptation goal should be considered.